2009
DOI: 10.1039/b804763b
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent ruthenium–polypyridine complexes & phosphorus ligands: anything but a simple story

Abstract: This tutorial review presents an exhaustive picture of the luminescence studies that have been undertaken on ruthenium(ii) complexes bearing polypyridine and phosphorus(iii) ligands. The introduction of phosphorus to the Ru coordination sphere has multiple consequences on the nature and energy of the various excited states involved, but it does not necessarily rule out room temperature emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…In a different approach, using high-spin ground state halogen-substituted Fe(terpy) 2 complexes, it was shown that the 5 T 2 to 5,7 MLCT transition can lead to ≈16 ps excited-state lifetimes, which presents a more than 100-fold increase with respect to traditional Fe-polypyridine complexes [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different approach, using high-spin ground state halogen-substituted Fe(terpy) 2 complexes, it was shown that the 5 T 2 to 5,7 MLCT transition can lead to ≈16 ps excited-state lifetimes, which presents a more than 100-fold increase with respect to traditional Fe-polypyridine complexes [29].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidized form of the mediator is finally regenerated by reduction at the cathode, thus forming a current source for electrical circuits. Ruthenium polypyridine complexes have long been considered as lead sensitizers due to their ideal photophysical and structural properties [4][5][6], allowing the attainment of up to 11% conversion efficiency [7][8][9]. Very high electron injection quantum yields [10][11][12] are at the origin of the remarkable success of these sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Polypyridines have attracted much attentions for their high binding affinity toward transition-metal ions,and have awide range of applications in OLEDs, dye-lasers, sensors and phototherapeutic reagents [2][3][4]. During our synthesis of some poly-dentated organic ligands and their metal ions complexes, we got the title compound, and report it structure here.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent metal ligand complexes used in bioanalytics and life sciences are ruthenium(II) complexes with ligands such as bipyridyl-or 1,10-phenenthroline derivatives [8,9] followed by platinum(II) and palladium(II) porphyrins [51]. Ru(II) coordination compounds absorb energy in the visible region of the spectrum (typically excitable at, e.g., 488 nm) or in the NIR depending on the ligand [52] populating a metal-to-ligand charge transfer ( 1 MLCT) state.…”
Section: Metal Ligand Complexesmentioning
confidence: 99%
“…There is an ever increasing toolbox of fluorescent labels and reporters to choose from: (1) molecular systems with a defined, yet versatility tunable chemical structure like small organic dyes [1,2], metal-ligand complexes (MLC) such as [Ru (bpy) 3 ] 2+ [8,9], and lanthanide chelates [10][11][12] as well as fluorophores of biological origin like phycobiliproteins and genetically encoded fluorescent proteins [3,13], (2) nanocrystal labels with size-dependent optical and physico-chemical properties which includes quantum dots (QDs) made from II/VI and III/V semiconductors [1,14], carbon [15] and silicon nanoparticles [16] as well as luminescent metal particles and clusters [17], self-luminescent organic nanoparticles [18], and (3) nanometer-sized upconversion phosphors as a new class of evolving inorganic nanocrystal labels with promising, partly size-dependent spectroscopic features composed of a crystalline host doped with emissive lanthanide ions (localized luminescent centers) [19]. (4) All these chromophores can be incorporated into nanometer-to micrometer-sized inorganic and organic polymeric particles, yielding multichromophoric particulate labels [20,21].…”
Section: Introductionmentioning
confidence: 99%